2013
DOI: 10.1002/cam4.159
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the mesothelium and lymphomatous cells: insight into the mechanisms involved in the progression of body cavity lymphomas

Abstract: The peculiar localization of body cavity lymphomas implies a specific contribution of the intracavitary microenvironment to the pathogenesis of these tumors. In this study, primary effusion lymphoma (PEL) was used as a model of body cavity lymphoma to investigate the role of mesothelial cells, which line the serous cavities, in lymphoma progression. The crosstalk between mesothelial and lymphomatous cells was studied in cocultures of primary human mesothelial cells (HMC) with PEL cells and a xenograft mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Due to the recently demonstrated shielding effect of the mesothelium on lymphoma progression [ 69 ], we then asked whether the mesothelial microenvironment protects against 2-DG+PF-04691502-facilitated apoptosis. To mimic the physiological microenvironment, BCBL1 cells were co-cultured with primary human mesothelial cells (HMC) for 48 hours, a condition sufficient to highlight the pro-survival effect of HMC on BCBL1 cells (Figure 6F ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the recently demonstrated shielding effect of the mesothelium on lymphoma progression [ 69 ], we then asked whether the mesothelial microenvironment protects against 2-DG+PF-04691502-facilitated apoptosis. To mimic the physiological microenvironment, BCBL1 cells were co-cultured with primary human mesothelial cells (HMC) for 48 hours, a condition sufficient to highlight the pro-survival effect of HMC on BCBL1 cells (Figure 6F ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is particularly important that the pro-apoptotic function of this drug association also prevails over the shielding action of the HMC in the HMC-BCBL1 co-culture performed to mimic the PEL microenvironment [ 69 ]. Finally, it is worth remembering that we have shown here that the above drug associations exert very low toxicity in normal human B and T lymphocytes, compared to PEL cells, suggesting some degree of specificity towards cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in vitro co-culture studies showed that mesothelial cells could modify the turnover of PEL cells by increasing their proliferation and their resistance to apoptotic stimuli, thus generating an environment favorable to PEL progression. 50 On the other hand, PEL cells, through the release of Transforming Growth Factor (TGF)-beta, induce type 2 epithelial-mesenchymal transition (EMT) in primary human mesothelial cells. 50 , 51 This can be observed in co-culture systems as well as in a preclinical animal model of SCID/PEL mimicking the aggressive nature of PEL in humans.…”
Section: Primary Effusion Lymphomamentioning
confidence: 99%
“… 50 On the other hand, PEL cells, through the release of Transforming Growth Factor (TGF)-beta, induce type 2 epithelial-mesenchymal transition (EMT) in primary human mesothelial cells. 50 , 51 This can be observed in co-culture systems as well as in a preclinical animal model of SCID/PEL mimicking the aggressive nature of PEL in humans. 28 Primary human mesothelial cells have a polygonal shape and form a regular monolayer in culture.…”
Section: Primary Effusion Lymphomamentioning
confidence: 99%